Knowledge, Practices, and Restrictions Related to Menstruation among Young Women from Low Socioeconomic Community in Mumbai, India - Thakur, Harshad; Aronsson, Annette; Bansode, Seema; Stalsby Lundborg, Cecilia; Dalvie, Suchitra; Faxelid, Elisabeth (Frontiers in Public Health, 2014)
The main objective was to assess knowledge, practices, and restrictions faced by young women regarding their menstrual hygiene. The views of adult women having young daughters were also included and both views were compared. In addition, the factors influencing the menstrual hygiene practices were also studied. The study was carried out during 2008 in Mumbai, India. The mixed methods approach was followed for the data collection. Both qualitative and quantitative methods were used to collect the data. For quantitative survey, totally 192 respondents (96 adult and 96 younger women) were selected. While young women were asked about questions related to their menstruation, adult women were asked questions to find out how much they know about menstrual history of their daughters. The qualitative data helped to supplement the findings from the quantitative survey and to study the factors affecting menstrual practices in young women. The mean age at menarche reported was 13.4 years and 30–40% of young girls did not receive any information about menstruation before menarche. It is thus seen that very few young girls between the age group 15 and 24 years did receive any information before the onset of menstruation. Among those who received some information, it was not adequate enough. The source of information was also not authentic. Both young and adult women agreed on this. Due to the inadequate knowledge, there were certain unhygienic practices followed by the young girls resulting in poor menstrual hygiene. It also leads to many unnecessary restrictions on young girls and they faced many health problems and complaints, which were either ignored or managed inappropriately. The role of health sector was almost negligible from giving information to the management of health problems of these young girls. This paper reemphasizes the important, urgent, and neglected need of providing correct knowledge to the community including adolescent girls.